O-227 Has time-lapse technology finally proven its clinical benefit?. (30th June 2022) - Armstrong, S; Pacey, A; Farquhar, C; Lensen, S
Abstract: Background: Time-lapse technology for the observation of embryos is not new, having been first described in 1930 by Dr WH Lewis using rabbit embryos. However, the use of software (using artificial intelligence and deep learning) linked to known clinical outcomes theoretically helps the embryologist select the 'best' embryo for embryo transfer. Time-lapse also reduces the need to manually handle embryos and is hypothesised would reduce biases due to interobserver variation and improve clinical outcomes. Whilst the technology may help improve laboratory workflow, the quantitative evidence is less clear. This raises the ethical question about charging extra for a technology which does not improve patient outcome. In offering time-lapse, professionals have argued that it responds to patient demand and the need to be seen as 'cutting edge'. However, the patient perspective for using time-lapse has, until recently, been largely unexplored. Methods: This presentation relies on three sources of evidence: (i) Systematic reviews of randomised controlled trials (RCTs) and newly published RCTs not yet incorporated into systematic reviews; (ii) Qualitative studies concerning the consideration or use of time-lapse in those undergoing IVF; and (iii) A qualitative study (VALUE) of patient professional views regarding time-lapse, amongst other add-ons. Results: The latest Cochrane systematic review undertook three comparisons to best establish where the potential advantage of time-lapse may lie: (i) undisturbed culture; (ii) the use of software to select the embryo to replace; or (iii) a combination of both stable culture and software. For all outcomes assessed, including crucially livebirth and miscarriage, there was no good evidence to show that time-lapse was any more or less effective than conventional methods of embryo incubation. These findings are supported by another systematic review by Chen et al (2017). A large RCT (TILT) is currently underway and will be the largest RCT to examine the clinical effectiveness and safety of time-lapse. TILT is expected to complete recruitment soon. The VALUE study is an international qualitative semi-structured interview study of patients, embryologists, and clinicians to explore the reasons behind the decisions to use non-evidence-based treatment 'add-ons' alongside an IVF cycle. Over half of patient participants interviewed opted to use time-lapse. Inductive thematic analysis revealed five key themes for patients: (i) 'vulnerability'; (ii) 'power of the trusted professional opinion'; (iii) 'role of previous experience'; (iv) 'acceptability of add-on'; and (v) 'the evidence doesn't apply to me'. The analysis of the professional participants' interviews revealed five themes, some of which mirror the patient themes: (i) 'treating desperation'; (ii) 'the patient shopper'; (iii) 'success not profits'; (iv) 'potential for harm'; and (v) 'tensions within evidence-based practice'. Discussion: Time-lapse has been adopted widely across fertility clinics globally, and with good reason. It brings efficiencies and convenience for embryologists by allowing them to observe embryos remotely. However, the highest quality evidence does not support the notion that it improves livebirth or reduces miscarriage rates. Qualitative research shows that patients can make choices about add-ons that can leave them in debt due to desperation and the desire to look for hope in an otherwise uncontrollable situation. Professionals acknowledge this, and in their desire to achieve a pregnancy, they sometimes look to add-ons such as time-lapse as a 'why not' when previous cycles have failed. Patients describe how they do not want to be denied time-lapse but want it in the context of informed consent. This must include being open about the paucity of evidence to support its effectiveness at this stage.